Risk Factors for Acute Hemorrhagic Rectal Ulcer Syndrome and Its Prognosis: A Density Case-Control Study. (8th August 2018) - Komai, Toshihiko; Omata, Fumio; Shiratori, Yasutoshi; Kobayashi, Daiki; Arioka, Hiroko
Abstract : Acute hemorrhagic rectal ulcer syndrome (AHRUS) can cause fatal gastrointestinal bleeding. However, there have been few epidemiological studies investigating risk factors of AHRUS. To determine the risk factors and predict one-year survival after onset of AHRUS, we conducted a retrospective density case-control study in a tertiary referral hospital. Patients with hematochezia, bloody stool, and rectal ulcer confirmed by colonoscopy between 2003 and 2011 were diagnosed as AHRUS (n = 38 ). Patients with malignancies, infectious colitis, ulcerative colitis, or solitary rectal ulcer syndrome were excluded. Control subjects (n = 123 ) without rectal ulcer were selected by risk set sampling for each AHRUS. Multivariate logistic regression analyses revealed that the significant adjusted odds ratio (95% confidence interval) of hospitalization, antithrombotic drug use, and one gram increase of serum albumin was 15.7 (2.25–108.9), 12.1 (1.53–94.4), and 0.11 (0.02–0.52), respectively. Endoscopic hemostasis for rectal bleeding was performed in 8 cases (21%). Seventeen percent of patients died within one year after the episode of AHRUS from non-AHRUS causes. This study revealed that hospitalization, antithrombotic drug use, and lower serum albumin value were significant risk factors for AHRUS, and that AHRUS was an unfavorable prognostic condition. This information could be helpful in recognizing high-risk patients of rectal bleeding and applying preventive measures.